Research on the Problems and Countermeasures in English Education for Chinese Children - Wang, Tianyi (Transactions on Social Science, Education and Humanities Research, 2024)
There are a series of problems in English education for Chinese children, and research on countermeasures to address these problems is becoming increasingly important. This study explores various problems and corresponding strategies from the perspective of English education for Chinese children. The research has found that Chinese children’s English education faces many problems such as language difficulty, cognitive challenges, and insufficient teaching resources. In response to these issues, some scholars have proposed a series of countermeasures, including improving the quality of English teachers, optimizing teaching methods and textbooks, and enriching teaching resources. In addition, the study also explored the possibility of using technological means to improve teaching effectiveness and called for greater emphasis on children’s English education in educational policies and curriculum arrangements. In summary, this study systematically explores the problems and countermeasures in English education for Chinese children, providing a useful reference for improving the quality of English education.